Overexpression of HTRA1 Leads to Down-Regulation of Fibronectin and Functional Changes in RF/6A Cells and HUVECs - Jiang, Jingjing; Huang, Lvzhen; Yu, Wenzhen; Wu, Xi; Zhou, Peng; Li, Xiaoxin (PLOS ONE, 2012)
Multiple genetic studies have suggested that high-temperature requirement serine protease (HTRA1) is associated with polypoidal choroidal vasculopathy (PCV). To date, no functional studies have investigated the biological effect of HTRA1 on vascular endothelial cells, essential vascular components involved in polypoidal vascular abnormalities and arteriosclerosis-like changes. In vitro studies were performed to investigate the effect of HTRA1 on the regulation of fibronectin, laminin, vascular endothelial growth factor (VEGF), platelet derived growth factor receptor (PDGFR) and matrix metalloparoteinases 2 (MMP-2) and the role of HTRA1 in choroid-retina endothelial (RF/6A) and human umbilical vein endothelial (HUVEC) cells. Lentivirus-mediated overexpression of HTRA1 was used to explore effects of the protease on RF/6A and HUVEC cells in vitro. HTRA1 overexpression inhibited the proliferation, cell cycle, migration and tube formation of RF/6A and HUVEC cells, effects that might contribute to the early stage of PCV pathological lesions. Fibronectin mRNA and protein levels were significantly down-regulated following the upregulation of HTRA1, whereas the expressions of laminin, VEGF and MMP-2 were unaffected by alterations in HTRA1 expression. The decreased biological function of vascular endothelial cells and the degradation of extracellular matrix proteins, such as fibronectin, may be involved in a contributory role for HTRA1 in PCV pathogenesis.